The sovereignty of art : aesthetic negativity in Adorno and Derrida - Menke, Christoph, 1958- (Studies in contemporary German social thought., 1998)
In this book, Christoph Menke attempts to explain art's sovereign power over reason without falling into an error common to Adorno's negative dialectics and Derrida's deconstruction. The error, which appeared even earlier in romanticism, is to conceive of the sovereignty of art as a reflection of the superiority of its knowledge; but art entails no knowledge, and its negativity toward reason cannot be articulated as an insight into the nature of reason. Rather, art is the medium of an experience that confronts reason from the outside with an insurmountable, never-ending crisis. Art is sovereign not despite, but because of, its autonomy. Its power to subvert reason depends on its separateness from reason. Menke brings to his arguments a firm grounding in both philosophy and literary studies, as well as familiarity with German, French, and American sources. -- Provided by publisher.